Hubungan Kualitas Pelayanan Dengan Kepuasan Pasien Rawat Inap Di RSUD Dr. Sayidiman Magetan - Yuliani, Umi, dr. N. Juni Triastuti, M. Med. Ed, dr. Mohammad Shoim Dasuki, M. Kes (2015)
Background: The service quality refers to the difference between hope and the fact received by the customers from the service providers. Satisfaction means disappointments or pleasure that someone experienced after comparing the result of a product or perception of performance with hopes. Recent study by Yeni in 2012 about health service quality and hospitalized patient in Sultan Daeng Radja obtained 58,1% respondents weren't satisfied with comfort they got. Dr. sayidiman general hospital of Magetan always tries their best to improve the service quality in order to achieve the target. The hospital effort to improve the service quality was increasing the specialist number, expansion of hospital buildings, and give some more service facilities. The purpose of this research is to know the association between quality of service with satisfaction of hospitalized patient in dr. Sayidiman General Hospital of Magetan. Methods: This study design was observational analytic with cross sectional method that define the connection between two variables, independent variable (quality of service) and dependent variable (patient satisfaction). The respondents of this study were hospitalized patient in the dr. Sayidiman General Hospital of Magetan taken with accidental sampling method. Total samples were 100 respondents. Data then analyzed with chi-square analysis test. Results: This research conducted with chi-square between service quality variables with patient satisfaction, with the result p < 0,0001. Conclusion: There is significancy relationship of service quality to satisfaction of hospitalized patient in dr. Sayidiman General Hospital of Magetan